Biological evaluation of porous aliphatic polyurethane/hydroxyapatite composite scaffolds for bone tissue engineering. Issue 7 (11th November 2014) - Yang, Wanxun; Both, Sanne K.; Zuo, Yi; Birgani, Zeinab Tahmasebi; Habibovic, Pamela; Li, Yubao; Jansen, John A.; Yang, Fang
Abstract: Biomaterial scaffolds meant to function as supporting structures to osteogenic cells play a pivotal role in bone tissue engineering. Recently, we synthesized an aliphatic polyurethane (PU) scaffold via a foaming method using non‐toxic components. Through this procedure a uniform interconnected porous structure was created. Furthermore, hydroxyapatite (HA) particles were introduced into this process to increase the bioactivity of the PU matrix. To evaluate the biological performances of these PU‐based scaffolds, their influence on in vitro cellular behavior and in vivo bone forming capacity of the engineered cell‐scaffold constructs was investigated in this study. A simulated body fluid test demonstrated that the incorporation of 40 wt % HA particles significantly promoted the biomineralization ability of the PU scaffolds. Enhanced in vitro proliferation and osteogenic differentiation of the seeded mesenchymal stem cells were also observed on the PU/HA composite. Next, the cell‐scaffold constructs were implanted subcutaneously in a nude mice model. After 8 weeks, a considerable amount of vascularized bone tissue with initial marrow stroma development was generated in both PU and PU/HA40 scaffold. In conclusion, the PU/HA composite is a potential scaffold for bone regeneration applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2251–2259, 2015.